O futuro importa: uma investigação exploratória da relação entre orientação de futuro e a percepção das mudanças climáticas - Farias, Alexandra Cavalcante de (2022)
Climate change (CC), a human-environmental problem that has its profound consequences from human action, presents a crisis character for this study and given its urgency, measures of mitigation need to be thought in the here and now, with repercussions a posteriori. The perception of climate change (pMCs), as outside our immediate and local context, can also generate a distance from perception of risk and an urgent need of commitment to mitigation actions. Thus, the relevance of future orientation (FO) should be considered as an attitudinal variable internal to individuals, which can be associated with pro-ecological commitment. In this way, it becomes important to identify whether, by taking responsibility for the generations not yet born, we are able to involve ourselves in environmental care actions or at least promote and engage our discourses in favor of sustainability. Considering this context, this study investigated the relationship between the perception of climate change and future orientation in the format of solidarity with future generations, aiming to understand the importance of future orientation to integrate the perception of climate change. The two studies that composed this exploratory investigation, carried out with 113 and 12 participants respectively, were organized using two different techniques: the production of a letter (even though in the first study it was contained in the questionnaire) and a semi-structured interview. The abductive content analysis originated thematic axes that dealt with pMCs and OF and were then analyzed from the perspective of the relationship between both concepts. The results demonstrated the importance of working with a temporal perspective when it comes to the phenomenon of MCs, and that it is not only possible to establish a bridge between pMCs and OF, but also to understand possible concepts that form this relationship. The perspective of solidarity with future generations reinforces its importance as a concept and the need to consider that future matters and that urgent changes are needed to guarantee an ecologically balanced environment.